2022
DOI: 10.3390/molecules27206984
|View full text |Cite
|
Sign up to set email alerts
|

Nipecotic Acid Derivatives as Potent Agents against Neurodegeneration: A Preliminary Study

Abstract: Alzheimer’s Disease (AD) is a common neurodegenerative disorder characterized by memory loss and cognitive impairment. Its pathology has not been fully clarified and therefore highly effective treatments have not been obtained yet. Almost all the current treatment options aim to alleviate only the symptoms and not to eliminate the disease itself. Acetylcholinesterase inhibitors are the main therapeutic agents against AD, whereas oxidative stress and inflammation have been found to be of great significance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Cinnamic acid and an array of its derivatives have been found to decrease carrageenan-induced inflammation, suppressing factors such as iNOS, COX-2 and NF-κB expression, as well as TNF-α [ 42 , 43 ]. Furthermore, we have shown that these 3-phenylacrylate moieties seem to enhance the anti-inflammatory potency in vivo and offer more than one pharmacological activity [ 32 , 33 , 35 ], whilst 3-(pyridin-3-yl)propan-1-ol insertion may offer movement towards this direction [ 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cinnamic acid and an array of its derivatives have been found to decrease carrageenan-induced inflammation, suppressing factors such as iNOS, COX-2 and NF-κB expression, as well as TNF-α [ 42 , 43 ]. Furthermore, we have shown that these 3-phenylacrylate moieties seem to enhance the anti-inflammatory potency in vivo and offer more than one pharmacological activity [ 32 , 33 , 35 ], whilst 3-(pyridin-3-yl)propan-1-ol insertion may offer movement towards this direction [ 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation was assessed spectrophotometrically (535/600 nm) as per the method using 2-thiobarbituric acid as the reagent. All compounds and solvents were found not to interfere with the assay [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cinnamic acids are reactive molecules due to possessing an unsaturated carbonyl moiety, which can be considered a Michael acceptor and benzene ring. Both make it possible to modify them, resulting in synthetic cinnamic acid derivatives with a broad range of biological properties, including antibacterial (Ruwizhi & Aderibigbe, 2020) antituberculosis (Teixeira et al, 2020), antimalarial (Fonte et al, 2023), antidiabetic (Adisakwattana, 2017;Feng et al, 2022), anticancer (Feng et al, 2022, antifungal (Liu et al, 2024), Alzheimer's treatment (Drakontaeidi & Pontiki, 2024), antioxidant (Nouni et al, 2023), andcosmetic (Gunia-Krzyz ˙ak et al, 2018). Among the various types of cinnamic acids documented, 4-pyridylacrylic acid (4-Hpya) is considered a highly valuable ligand because of several structural characteristics that make it suitable for the construction of coordination compounds.…”
Section: Chemical Contextmentioning
confidence: 99%